INDIVIDUALITY OF KINDERGARTEN TEACHERS - Nesyna, Svetlana Vadimovna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
This article focuses on the problem of individuality. The theoretical basis is O. Grebenyuk’s individuality concept. In it, the individuality is defined as the unity of intellectual, motivational, volitional, emotional, practical and object-oriented, existential and self-regulative spheres which characterise the originality and uniqueness of a person. The term ‘individuality of a teacher’ refers to an integrated and holistic system of seven interconnected spheres, including professionally important components which differentiate it from the individuality of other subject of a professional avtivity. This study adresses three key issues. First, it looks at the problem of preschool teacher’s individuality and identifies the system of professionally important components. Second, it turns to examine the professional deformations of teachers. Finally, the paper considers the relationships between the individuality system and types of professional destructions in the groups of preschool teachers of different age and with different professional experience. The data for this study were collected using the questionnaires: “The Technique of Teacher’s Individuality” by T. B. Grebenyuk and “The Method for Studing Professional Teacher’s Deformations”by E. F. Zeer. Fifty-two teahers were recruited for this study. The participants work at various kindergartens in the Kaliningrad region. The results suggest that the motivational and existential spheres are developed most strongly. The most exrpessed professional deformation is demonstrativeness. Statistical analyses revealed two types of correlations: 1) a positive correlation between the intellectual, motivational, and practical and object-oriented spheres with demonstrativeness; 2) a negative correlation between the emotional sphere and dogmatism.